Physician View and Experience of the Diagnosis of Autism Spectrum Disorder in Young Children - Jacobs, Delphine; Steyaert, Jean; Dierickx, Kris; Hens, Kristien (Frontiers in Psychiatry, 2019)
Introduction Clinicians working with children with autism spectrum disorder (ASD) occupy an important position between parents and the wide-ranging research findings. However, it is not widely known how clinicians experience and view ASD in children, even though their perspective has been shown to significantly influence their work. Material and methods Sixteen physicians working with not-disabled preschool children with a (presumed) diagnosis of ASD participated in a semi-structured interview. They described their professional views on ASD, and how they experienced its use in their clinical practice. Results Interpretative phenomenological analysis of the data through Nvivo 11 revealed the main topic of physicians' conceptualizations of ASD in a young child. This topic comprised three inductively established themes: (1) physicians' views on ASD are multifaceted but fit within their personal clinical styles; (2) the ASD diagnosis is a "descriptive" part of a clinical trajectory; and (3) ASD treatment is a personalized search. Physicians' perspectives on ASD are composed of multiple and sometimes ambiguous facets. However, their perspectives are embedded in their personal clinical styles in general (i.e. beyond ASD) and are experienced as clinically "workable". With the aim of finding an adequate approach to the problems parents bring to their office, physicians often say that - rather than a classificatory diagnosis - they prefer using a personalized "profile" of a child in a therapeutic "process". Conclusions The interviewed physicians consider doubts and concerns to be an inherent part of their clinical work with ASD in young children, but do not experience this ambiguity as an obstacle to clinical care. These physicians deal with the multiplicity of their views on ASD by basing their eclectic views on their generally adopted clinical styles, and by selecting what works for them, and for the parents and child, from what they regard as the 'textbook knowledge' on ASD.